1997
DOI: 10.1152/jn.1997.78.1.492
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Compressive Responses of Nociceptors in Rat Hairy Skin

Abstract: Mechanically sensitive nociceptor afferents were studied in a preparation of isolated skin from rat leg. Each neuron was studied while the skin was subjected to tensile and compressive loading. The experiment was designed to create highly uniform states of stress in both tension and compression. Tensile loads were applied by pulling on the edges of the sample. Applied loads were used to determine the tensile stresses. Surface displacements were used to determine tensile strains. Compressive loads were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 38 publications
(9 reference statements)
5
73
4
Order By: Relevance
“…In our study, 3D strain tracking was incorporated with neurophysiological recordings. Other studies on mechanosensitive afferents have suggested that the correlation between nerve response and local stress was better than local strain in skin [11,16] and knee joint [8,15]. High coefficients were observed in both strain correlation and load correlation with neural responses in current study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, 3D strain tracking was incorporated with neurophysiological recordings. Other studies on mechanosensitive afferents have suggested that the correlation between nerve response and local stress was better than local strain in skin [11,16] and knee joint [8,15]. High coefficients were observed in both strain correlation and load correlation with neural responses in current study.…”
Section: Discussionsupporting
confidence: 58%
“…All 2D stress studies with neurophysiology have been performed in vitro on clearly isolated and easily accessible tissues, such as skin [16] and limb muscle [9]. However, because spine FJCs are small and hard to access in vivo, it is rather difficult to accommodate multiple load cells, which are required to measure 2D stress during tensile tests.…”
Section: Discussionmentioning
confidence: 99%
“…At these hot spots, the stimulus-response functions of C-fiber nociceptors reached a plateau at force levels substantially below the pain threshold (Greenspan and McGillis, 1991;Khalsa et al, 1997;Andrew and Greenspan, 1999;Slugg et al, 2000). The flatness of the stimulus-response curves suggested that C-fiber nociceptors could not encode painfulness of punctate mechanical stimuli.…”
Section: Stimulus-response Functions and Psychophysical Correlationsmentioning
confidence: 99%
“…Because the preparation of rat skin (Khalsa et al 1997) and the apparatus (Del Prete et al 2003) are described in detail elsewhere, they are only briefly described here.…”
Section: E T H O D Smentioning
confidence: 99%